2010
DOI: 10.1093/icesjms/fsp288
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal variability in cetacean distribution in the fjords of northern Patagonia, Chile

Abstract: Viddi, F. A., Hucke-Gaete, R., Torres-Florez, J. P., and Ribeiro, S. 2010. Spatial and seasonal variability in cetacean distribution in the fjords of northern Patagonia, Chile. – ICES Journal of Marine Science, 67: 959–970. Compared with other Chilean coastal areas, little is known about the diversity and distribution of cetaceans in northern Patagonian fjords. Between December 2000 and November 2001, surveys on platforms of opportunity were undertaken in southern Chile to evaluate species richness and the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
74
0
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 41 publications
7
74
0
12
Order By: Relevance
“…Our results confirmed that Peale's dolphin and Chilean dolphin are the most frequent small cetacean species (65.5% and 20.2% of the sightings respectively) that inhabit in most of the sheltered areas of southern Chile as it has been documented in the region (Goodall et al 1988, 1997, Goodall 1994, Viddi et al 2010). An exception is the eastern Strait of Magellan where Commerson's dolphin is the most common one (Lescrauwet et al 2000).…”
supporting
confidence: 88%
See 4 more Smart Citations
“…Our results confirmed that Peale's dolphin and Chilean dolphin are the most frequent small cetacean species (65.5% and 20.2% of the sightings respectively) that inhabit in most of the sheltered areas of southern Chile as it has been documented in the region (Goodall et al 1988, 1997, Goodall 1994, Viddi et al 2010). An exception is the eastern Strait of Magellan where Commerson's dolphin is the most common one (Lescrauwet et al 2000).…”
supporting
confidence: 88%
“…In this last area a summer aggregation of humpback whales has been reported as well (Galletti et al 20062 , 20083 , Hucke-Gaete et al 2006 ), and photographic identification has confirmed movements and interchange of humpback whales individuals within the Strait of Magellan near Carlos III Island (Capella et al 2008 (Viddi et al 2010). Mysticetes were distributed along a north -south gradient with preferences for open gulfs with oceanic influence, and close to shore.…”
mentioning
confidence: 76%
See 3 more Smart Citations